Carnosol inhibits inflammasome activation by directly targeting HSP90 to treat inflammasome-mediated diseases - Shi, Wei (Cell Death Dis, 2020)
Aberrant activation of inflammasomes, a group of protein complexes, is pathogenic in a variety of metabolic and inflammation-related diseases. Here, we report that carnosol inhibits NLRP3 inflammasome activation by directly targeting heat-shock protein 90 (HSP90), which is essential for NLRP3 inflammasome activity, thereby treating inflammasome-mediated diseases. Our data demonstrate that carnosol inhibits NLRP3 inflammasome activation in primary mouse bone marrow-derived macrophages (BMDMs), THP-1 cells and human peripheral blood mononuclear cells (hPBMCs). Mechanistically, carnosol inhibits inflammasome activation by binding to HSP90 and then inhibiting its ATPase activity. In vivo, our results show that carnosol has remarkable therapeutic effects in mouse models of NLRP3 inflammasome-mediated diseases, including endotoxemia and nonalcoholic steatohepatitis (NASH). Our data also suggest that intraperitoneal administration of carnosol (120 mg/kg) once daily for two weeks is well tolerated in mice. Thus, our study reveals the inhibitory effect of carnosol on inflammasome activation and demonstrates that carnosol is a safe and effective candidate for the treatment of inflammasome-mediated diseases.